Pengaruh Penggunaan SIMRS Terhadap Efektivitas Kinerja Staff Keuangan di Rumah Sakit X - Ernikowati, Vira Cahya Inkai; Fitriyani, Sani (Barongko: Jurnal Ilmu Kesehatan, 2024)
Every hospital is required to record and report all hospital operations in the form of a hospital management information system. In addition, hospital management needs data that is reliable, accurate, timely, secure and relevant from an administrative and clinical perspective. The method used in this research is qualitative by collecting data through interviews and observations. The results of the interviews show that SIMRS has been used since 2022, previously Hospital X used a manual system, namely the VB module. The data entry process is very simple compared to before, the functions used include hospital accounts, statements and invoices. This system also provides benefits, namely by reducing time, increasing the efficiency of financial staff performance, supporting the data entry process and reducing manual work. Although it works effectively, there are obstacles such as poor connections that can prevent this system from working effectively.